A Novel Highly Bioavailable Curcumin Formulation Improves Symptoms and Diagnostic Indicators in Rheumatoid Arthritis Patients: A Randomized, Double-Blind, Placebo-Controlled, Two-Dose, Three-Arm, and Parallel-Group Study - Amalraj, Augustine; Varma, Karthik; Jacob, Joby; Divya, Chandradhara; Kunnumakkara, Ajaikumar B; Stohs, Sidney J; Gopi, Sreeraj (Journal of medicinal food, 2017)
Rheumatoid arthritis (RA) is an autoimmune, chronic systemic inflammatory disorder. The long-term use of currently available drugs for the treatment of RA has many potential side effects. Natural phytonutrients may serve as alternative strategies for the safe and effective treatment of RA, and curcuminoids have been used in Ayurvedic medicine for the treatment of inflammatory conditions for centuries. In this study, a novel, highly bioavailable form of curcumin in a completely natural turmeric matrix was evaluated for its ability to improve the clinical symptoms of RA. A randomized, double-blind, placebo-controlled, three-arm, parallel-group study was conducted to evaluate the comparative efficacy of two different doses of curcumin with that of a placebo in active RA patients. Twelve patients in each group received placebo, 250 or 500 mg of the curcumin product twice daily for 90 days. The responses of the patients were assessed using the American College of Rheumatology (ACR) response, visual analog scale (VAS), C-reactive protein (CRP), Disease Activity Score 28 (DAS28), erythrocyte sedimentation rate (ESR), and rheumatoid factor (RF) values. RA patients who received the curcumin product at both low and high doses reported statistically significant changes in their clinical symptoms at the end of the study. These observations were confirmed by significant changes in ESR, CPR, and RF values in patients receiving the study product compared to baseline and placebo. The results indicate that this novel curcumin in a turmeric matrix acts as an analgesic and anti-inflammatory agent for the management of RA at a dose as low as 250 mg twice daily as evidenced by significant improvement in the ESR, CRP, VAS, RF, DAS28, and ACR responses compared to placebo. Both doses of the study product were well tolerated and without side effects.